Primary Breast Cancer Tumor and Patient Characteristics as Predictors of Adjuvant Radiation Therapy. Issue 1 (26th September 2016) - VanderBeek, Laura; Francescutti, Valerie; Farrokhyar, Forough; Lovrics, Peter; Strang, Barbara; Kahnamoui, Kamyar
Abstract: Adjuvant radiation therapy reduces the risk of local recurrence of breast cancer. Our study identifies patient and tumor characteristics that guide the use of adjuvant radiation therapy and evaluates our adherence to recommended guidelines. A retrospective review was undertaken of 1, 667 stage I–III breast cancer patients treated at a regional cancer center from 2004 to 2007. Univariate analysis was used to select factors for entry into a multivariate stepwise logistic regression model. Descriptive statistics was used to compare use of radiation therapy of 382 stage I–III breast cancer patients diagnosed in 2013 to those from 2004 to 2007. The primary indicators for any radiation therapy ( n = 935) were breast conserving surgery (OR 79.5, 95% CI [47.6–132.9]), four to nine positive lymph nodes (71.9, [17.0–304.7]), and greater than nine positive lymph nodes (60.5, [7.9–460.8]). In post‐mastectomy patients ( n = 408), the indicators for radiation therapy were four to nine positive lymph nodes (29.4, [12.9–67.4]) and greater than nine positive lymph nodes (108.3, [14.5–807.5]). In breast conserving surgery patients ( n = 1, 081) 96.1% were offered radiation therapy. Patients offered local‐regional radiation therapy were more likely to have any positive nodes (ORs 4.3–91.0), have had a mastectomy (4.3, [2.2–8.4]), and had larger tumors (1.6, [1.3–2.0]). Local‐regional radiation therapy was recommended less frequently in node positive patients in 2004–2007 (35.0%) compared to in 2013 (70.5%) [p < 0.001]. Patients who had a breast conserving surgery or had four or more positive lymph nodes were more likely to receive radiation therapy. Patients with any positive lymph nodes, larger tumors, or who had a mastectomy were more likely to receive local‐regional radiation therapy. Our institution was more likely to offer local‐regional radiation therapy in node positive breast cancer in 2013 compare to 2004–2007.